Predictors for rTMS response in chronic tinnitus - Lehner, Astrid; Schecklmann, Martin; Landgrebe, Michael; Kreuzer, Peter M.; Poeppl, Timm B.; Frank, Elmar; Vielsmeier, Veronika; Kleinjung, Tobias; Rupprecht, Rainer; Langguth, Berthold (Frontiers in Systems Neuroscience, 2012)
Background: Repetitive transcranial magnetic stimulation (rTMS) has been studied as a treatment option for chronic tinnitus for almost 10 years now. Although most of these studies have demonstrated beneficial effects, treatment results show high interindividual variability and yet, little is known about predictors for treatment response. Methods: Data from 538 patients with chronic tinnitus were analyzed. Patients received either low-frequency rTMS over the left temporal cortex (n = 345, 1 Hz, 110% motor threshold, 2000 stimuli/day) or combined temporal and frontal stimulation (n = 193, 110% motor threshold, 2000 stimuli at 20 Hz over left dorsolateral prefrontal cortex plus 2000 stimuli at 1 Hz over temporal cortex). Numerous demographic, clinical, and audiological variables as well as different tinnitus characteristics were analyzed as potential predictors for treatment outcome, which was defined as change in the tinnitus questionnaire (TQ) score. Results: Both stimulation protocols resulted in a significant decrease of TQ scores. Effect sizes were small, however. In the group receiving combined treatment, patients with comorbid temporomandibular complaints benefited more from rTMS than patients without those complaints. In addition, patients with higher TQ scores at baseline had more pronounced TQ reductions than patients with low TQ baseline scores. Also, patients who had already improved from screening to baseline benefited less than patients without initial improvement. Conclusions: The results from this large sample demonstrate that rTMS shows only small but clinically significant effects in the treatment of chronic tinnitus. There are no good demographic or clinical predictors for treatment outcome.